دور الافصاح غير المالي عن تنمية الموارد البشرية في مكافحة الفساد - أوبان عبد الله (Latakia University Journal - Economic and Legal Sciences Series, 2018)
أصبح الفساد ظاهرة عالمية على مستوى الأفراد والدول سواء كانت متقدمة أو متخلفة. وتؤكد العديد من التقارير والمنظمات الدولية ومنها منظمة الشفافية الدولية والبنك الدولي، أن الفساد هو عقبة تعترض طريق التنمية الاقتصادية والاجتماعية. وإذا كانت الحكومات تقوم بمحاربة الفساد الإداري وترشيد إدارة المال العام وتطوير وسائل الرقابة والمحاسبة، فان نجاح ذلك يعتمد على كفاءة المنظومة الإدارية التي تُعنى بوضع الأهداف والخطط ووسائل الرقابة والمتابعة والتقييم، لان كفاءةً أفضل للإدارة من شأنها، إذا ما ترافقت بشفافية أعلى أن تحد من الفساد. وتتجلى الاختلاسات والاحتيال المالي في نتائج الأعمال والمراكز المالية التي تنتج بممارسات تقوم بها الموارد البشرية، أما بتضخيم نتائج الأعمال والمراكز المالية أو بتخفيض نتائج الأعمال والمراكز المالية. يهدف هذا البحث الى التعريف بأنواع الفساد الموجودة في البيئة السورية ومتابعة وتقييم الجهود المبذولة لمواجهتها. وكذلك التعرف على مؤشر مدركات الفساد، بهدف توجيه الدفة نحو تعزيز الالتزام السياسي لصالح محاربة فعالة ضد الفساد خصوصا ً في ظل سياق خطاب السيد رئيس الجمهورية الدكتور بشار الاسد الذي ركز فيه على الاصلاح الاداري. وكما يهدف هذا البحث الى الكشف عن الافصاح الطوعي والاجتماعي بشكل عام وعن تنمية الموارد البشرية للشركات العربية ودوره في مكافحة بالفساد. اعتمد البحث دراسة حالة وصفية تحليلية عن الافصاح عن تنمية الموارد البشرية في مكافحة الفساد. توصلت الدراسة الى ان المحاسبة و المراجعة هما اساسا ً من الانظمة التي تكفل وضع الاجراءات الوقائية لتجنب الغش والفساد المالي والاداري قبل وقوع اي حوادث من هذا النوع. وإن الاصلاح الاداري يتطلب مكافحة الفساد ولن ينجح هذا الاصلاح إلا بتنمية الموارد البشرية وتظافر الجهود المشتركة بين القطاع العام والخاص. حيث يضمن ذلك رفع كفاءة العمل في المنظّمات مما يساهم أيضاً في زيادة الارباح التشغيلية. Corruption has become a global phenomenon at the level of individuals and countries, whether developed or undeveloped countries. Many international reports and organizations, including Transparency International organization and the World Bank, confirm that corruption is an obstacle to economic and social development. If governments fight against administrative corruption, rationalize the management of public funds and develop means of monitoring and accountability, the success depends on the efficiency of the administrative system. Fraud and financial fraud are reflected in the results of business and their financial reports, carried out by human resources, either by increasing the profits of business and financial position or by reducing their profits. The purpose of this study is to identify the types of corruption in the Syrian environment, to follow up and evaluate the efforts against them. And to identify the corruption perception index, with the aim of guiding the political commitment against corruption, especially in the context of the speech of President Bashar al-Assad, in which he insisted on the administrative reform. The aim of this research is also to reveal voluntary and social disclosure in general and to develop the human resources of Arab companies and their role in fighting corruption. This research is based on an analytical descriptive case study on the disclosure of human resources development against corruption. This research concluded that accounting and auditing are basically systems that ensure the establishment of preventive measures to avoid fraud and financial and administrative corruption. Administrative reform requires instruments in the fight against corruption. This reform will be successful only and through the development of human resources, with joint efforts between the public sector, the private sector and civil society. Hence, this ensures that the efficiency of the organizations work and outcomes are increased, which contributes also to increase their operational profits.